Introduction: displacement, asylum and the city – theoretical approaches and empirical findings. Issue 7 (9th August 2021) - Kreichauf, René; Glorius, Birgit
ABSTRACT: Forced migration is an urban phenomenon – an integral part of twenty-first century urban landscapes, as well as an "urban story" of those displaced. In this introductory article, we draw attention to the interlinked yet understudied relationship between the role of cities in dealing with the arrival of forced migrants and the influence of forced migration in stimulating spatial, societal, and institutional transformations in and of cities. Seeking in an interdisciplinary way to urbanize debates on forced migration, we analyze and structure current literature and forced migration trends, and link them to urban theory, while contextualizing the contributions of this special issue. This reveals not only how forced migration unfolds in urban contexts, but also how it changes the urban realm and the way we think about cities. Accordingly, we propose ideas for future research, adding to discussions about re-theorizing "the urban" and including urban aspects in forced migration studies.